Dz2 orbital-mediated bound magnetic polarons in ferromagnetic Ce-doped BaTiO3 nanoparticles and their enriched two-photon absorption cross-section. Issue 7 (4th February 2019) - Senthilkumar, P.; Dhanuskodi, S.; Karthikeyan, J.; Murugan, P.
Abstract : Oxygen vacancy-triggered ferromagnetism and two-photon absorption cross-section of Ce-doped BaTiO3 nanoparticles: combined theoretical and experimental insights. Abstract : The enriched ferromagnetism and two-photon absorption (TPA) cross-section of perovskite BaTiO3 nanoparticles are indispensable for magnetic and optical data storage applications. In this work, hydrothermally synthesized Ce-doped BaTiO3 nanoparticles exhibited the maximum room temperature ferromagnetism (4.26 × 10 −3 emu g −1 ) at 4 mol% due to the increase in oxygen vacancies, as evidenced by X-ray photoelectron and electron spin resonance spectroscopy and density functional theory (DFT) calculations. Hence, the oxygen vacancy-constituted bound magnetic polaron (BMP) model was invoked to explain the enhancement in ferromagnetism. The BMP theoretical model indicated an increase in BMP magnetization ( M 0, 3.0 to 4.8 × 10 −3 emu g −1 ) and true spontaneous moment per BMP ( m eff, 4 to 9.88 × 10 −4 emu) upon Ce doping. DFT calculations showed that BMPs mediate via the Ti d z 2 orbitals, leading to ferromagnetism. Besides, it is known that the magnetic moment induced by Ce at the Ba site is higher than Ce at the Ti site in the presence of oxygen vacancies. The open aperture Z-scan technique displayed the highest TPA coefficient, β (7.08 × 10 −10 m W −1 ), and TPA cross-section, σ TPA (455 × 10 4 GM), at 4 mol% of Ce as a result of the robust TPA-induced excited state absorption. The large σ TPA is attributed to the longer excited state lifetime, τ (7.63 ns), of the charge carriers created by oxygen vacancies and Ce ions, which encounter several electronic transitions in the excited sub-states.